Organização e funcionamento da política representativa local : o caso do município de São Carlos - Martins, Thais Cavalcante (Universidade Federal de São Carlos, 2015)
This research aims to examine the organization and functioning of representative politics in São Carlos between the years 2001-2008, including the way that political representation is exercised at the local level. We seek to identify and analyze the profile of local political elites, the strategies adopted by councilors in the performance of representation as well as the relationship established with the executive. To this end, we look back on the local scene from the resumption of the political divide, the rules of the legislative process, in addition to the agenda approved by the mayor and the City Council. The study seeks to demonstrate that the choice made by political actors would be related, as far as possible, to the unique dynamics of county policy. Although individuals are the basic unit of analysis, they operate according to the parameters set by the institutional environment in which they operate. Are the preferences of the actors as well as its position in the political game that make these opt for a strategy or other possibilities in the field of institutional rules.
Keywords: Política local; Relação Executivo - Legislativo; Partidos políticos; Representação política; Local politics; Relationship executive-legislature; Political parties; Political representation; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO